Comparison of a Numerical Weather Prediction Model with two different Horizontal Resolutions for North-West Iceland: An Analysis of the skill of the Harmonie-Arome model at 2.5 km and 750 m horizontal resolutions - Páll Ágúst Þórarinsson 1995- (2019)
The purpose of this research is to analyse the performance of a numerical weather prediction model with two different horizontal resolutions, 2.5 km and 750 m in North-West Iceland. The data and model output used were derived from the numerical weather prediction model (NWP) Harmonie-Arome and from automatic weather stations in the forecast area. The analysed data were GRIB files and time series extracted from the files that were used for verification. The verification is made by comparing simulated values at individual points with observations and by visual inspection of entire fields of wind and temperature for both horizontal resolutions. The results indicate that the simulations generated too much wind for both resolutions. By increasing the horizontal resolution from 2.5 km to 750 m the simulations showed significant improvements in simulating wind at locations in complex terrain. Extreme errors in the wind simulation were almost eliminated by the higher resolution simulation’s ability to reproduce the terrain better. When applying elevation correction to the temperature the number of extreme errors increased, which may be attributed to an increase in temperature variability. Results of visual comparison of weather maps showed more details for the 750 m than for the 2.5 km horizontal resolution, both for the simulated temperature and wind fields. Markmið þessarar rannsóknar er að greina frammistöðu reiknilíkans fyrir veðurspár á Norðvesturlandi í tvenns konar reiknimöskvum, annars vegar 2,5 km og hins vegar 750 m. Reiknigögnin eru úr veðurspárlíkaninu (e. NWP) Harmonie-Arome og mælingar frá sjálfvirkum veðurstöðvum á spásvæðinu voru notuð til sannprófunar. Sannprófunin fólst annars vegar í að bera saman punktspá og athuganir og hins vegar í samanburði á veðurkortum fyrir hitastig og vind úr reiknilíkani fyrir báðar möskvastærðirnar. Niðurstöður benda til að reiknilíkanið spái of miklum vindi í báðum reiknimöskvum. Með því að þétta möskvana frá 2,5 km í 750 m batnar veðurspáin fyrir vind umtalsvert á ...